2017
DOI: 10.1038/s41598-017-11768-y
|View full text |Cite
|
Sign up to set email alerts
|

The causes and ecological correlates of head scale asymmetry and fragmentation in a tropical snake

Abstract: The challenge of identifying the proximate causes and ecological consequences of phenotypic variation can be facilitated by studying traits that are usually but not always bilaterally symmetrical; deviations from symmetry likely reflect disrupted embryogenesis. Based on a 19-year mark-recapture study of >1300 slatey-grey snakes (Stegonotus cucullatus) in tropical Australia, and incubation of >700 eggs, we document developmental and ecological correlates of two morphological traits: asymmetry and fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 66 publications
4
12
0
Order By: Relevance
“…This type of asymmetry occurs when developmental errors resulting from exogenous environmental conditions experienced during embryogenesis produce asymmetry in morphological traits normally distributed around a mean of zero ( Palmer & Strobeck, 2003 ). Fluctuating asymmetry occurs in bilaterally symmetrical body parts such as wings ( Hoffmann, Collins & Woods, 2002 ; Hoffmann et al, 2005 ), head capsules ( Leamy et al, 2015 ), jaws ( Wiig & Bachmann, 2014 ), and scales ( Brown et al, 2017 ). It is distinct from other types of asymmetry including directional asymmetry, where the population mean of the left right differences do not equal zero, and antisymmetry, where asymmetry is the norm but asymmetry towards the left and right sides are equally common, that is normally distributed around a mean of zero ( Klingenberg, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This type of asymmetry occurs when developmental errors resulting from exogenous environmental conditions experienced during embryogenesis produce asymmetry in morphological traits normally distributed around a mean of zero ( Palmer & Strobeck, 2003 ). Fluctuating asymmetry occurs in bilaterally symmetrical body parts such as wings ( Hoffmann, Collins & Woods, 2002 ; Hoffmann et al, 2005 ), head capsules ( Leamy et al, 2015 ), jaws ( Wiig & Bachmann, 2014 ), and scales ( Brown et al, 2017 ). It is distinct from other types of asymmetry including directional asymmetry, where the population mean of the left right differences do not equal zero, and antisymmetry, where asymmetry is the norm but asymmetry towards the left and right sides are equally common, that is normally distributed around a mean of zero ( Klingenberg, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A consensus about this issue still cannot be fully established as some analyses have showed that trait type does not have a predictive power in FA studies [45]. With regard to reptiles, contradictory results [11,46] point to the necessity of more elaborated studies, but the use of FA cannot be rejected as the latest long-term studies [47] and meta-analyses [48] have shown that ecological correlates and causes of asymmetry can be detected.…”
Section: Discussionmentioning
confidence: 99%
“…1A)). The temporal row was treated as in Brown et al (2017). All scales around the eye (subocular, preocular, supraocular and postocular) were treated as perioculars, as applied previously (Bellaagh et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on asymmetry in reptiles are relatively new, geographically biased and focus mainly on lizards and less on snakes (Laia et al 2015), although more recent studies have appeared in literature (Brown et al 2017;Löwenborg and Hagman 2017). In order to remedy this deficiency, studies on this topic are necessary, the more so because asymmetry seems to measure developmental stability in stressful conditions (Laia et al 2015).…”
Section: Introductionmentioning
confidence: 99%